REHABILITASI SOSIAL EKONOMI BERBASIS SYARIAH BAGI KORBAN NAPZA DI YAYASAN GRAPIKS KABUPATEN BANDUNG - Srisusilawati, Popon; Putra, Panji Adam Agus; Utami, Ayu Tuty; Siregar, Ariani; Rois, Yovanka Graciela; Tahany, Tahany; Rosyidah, Fairuz Syifa (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2020)
The purpose of the implementation of sharia-based social economic rehabilitation PKM activities for drug victims in the Grapiks foundation in the village of Cimekar, Cileunyi, Bandung, Bandung, is to provide solutions to the problems that have been faced, namely the tendency of former drug users to re-use very large. Rejection from families and the environment against drug victims, this rejection is related to their survival in economic terms, so they need skills development and how to socialize again with the surrounding community. Therefore the application of the sharia system in socio-economic rehabilitation is very important for drug victims who have an impact on the level of the economy and the welfare of former drug victims. It is clear that the psychic and economic condition of the former victim of this drug needs to be developed with sharia-based social economic rehabilitation. The specific target to be achieved is the change in behavior of former victims of drugs. Increasing the quality of SDI victims of drugs. The method used is the first approach to assisting behavioral change carried out continuously by involving family or spouse. Second, business / skill assistance is by exploring the potential of a former drug victim. The activities carried out are assisting with behavioral change by instilling Islamic principles so that they can go back to the community, explore the potential of drug victims by providing entrepreneurial training in accordance with Islamic law. Assistance is carried out until the end of the PKM program and after the PKM program ends. As a result of the PKM there was an increase in understanding of diversity regarding drugs and increasing the skills of drug victims.